Penggunaan Syarat Ketertiban Sebagai Dasar Pembatalan Putusan Arbitrase Internasional Di Indonesia - Diangsa Wagian (Jatiswara, 2011)
The research aims to study the competence of the District Court of Central Jakarta to annul the arbitration award of Geneva, and whether the judgment of the District Court of Central Jakarta annulling the arbitration award of Geneva is relevant to the existing law of arbitration in Indonesia. The research is juridical normative, i.e., using library research to obtain secondary data in the field of law and using field research for support. Therefore, it uses two types of data: primary data from interview with resource persons and secondary data from library research by means of document study on the primary, secondary, and tertiary legal materials. It uses qualitative method to analyze the data. The research reveals, according to the Arbitration Law No. 30 of 1999, Regulation of the Supreme Court No. 1 of 1990, Rules of International Centre for Settlement of Investment Disputes, and New York Convention 1958, that the District Court of Central Jakarta has no competence to annul the arbitration award of Geneva. The use of public policy as ground for annulment of arbitration award of Geneva by Forum of District Court of Central is not correct because public policy is not found, ether in Rules of International Centre for Settlement of Investment Disputes or New York Convention 1958, as ground for annulment of arbitration award. Besides, public policy provided in the Arbitration Law No. 30 of 1999, Regulation of The Supreme Court No. 1 of 1990, and New York Convention 1958 is not related to the annulment of international arbitration award but the refusal and enforcement of international arbitration award. Nevertheless, Forum Court's interpretation toward public policy is correct because such interpretation is not based on assumption but on the fact that the enforcement of arbitration award of Geneva violates the Presidential Decree No. 39 of 1997 and No. 5 of 1998, as well as the monetary crisis threatening Indonesian prosperity.